Revisiting Market-Level Competition: The Perspective from Low-Cost Entrants - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2012)
In view of the persistently high failure rate of new entrants, this paper proposes a ‘survival-first, profit-second’ market entry strategy for young, de novo low-cost entrants in an industry dominated by higher-cost and higher-quality incumbents. Aimed at minimizing retaliation from incumbents, this strategy advises low-cost entrants to aim at customers not already served by the incumbents, and to adopt Cournot-type behavior when encountering fellow low-cost competitors. Several hypotheses developed from a formal model were tested using data from the intra-European airline industry, and were broadly supported. Contrary to intuition, the presence of many high-quality incumbents significantly reduced the profit for low-cost entrants, as witnessed by the increased the probability of market exit by a focal low-cost entrant.